(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This article reviews Phoenician and Punic inscriptions found in and around the Iberian Peninsula, which have been discovered or published in recent years (from 2009 year of the 10th International Congress of Palaeohispanic Cultures and Languages held in Lisbon until 2012 year of the 11th Congress held in Valencia). The text presents, contextualizes and analyses each new document and briefly discusses its epigraphic and historical interest.